What Might Be the Future of Our Profession: Gazing into a Murky Crystal Ball. Issue 4 (April 2017) - Kaufman, Roger
Abstract : We can, as a profession armed with valid research‐based concepts and methods, help to measurably improve our shared world and to transform our society from its current trajectory to a welcoming place for tomorrow's children (Mega thinking and planning). The alternatives lead to a dreary and self‐defeating path.